A anotação sintáctica do CORDIAL-SIN - Carrilho, Ernestina (2018)
The annotated dialect corpus CORDIAL-SIN provides straightforward and systematic access to a compilation of spontaneous and semi-directed speech from European Portuguese dialects. Optimal inquiry for precise morphological and syntactic information throughout this corpus is granted by two layers of annotation (part-of-speech tagging and syntactic annotation), which are automatically searchable for linguistic labels and structures through independently available tools. This paper concentrates on issues pertaining to the CORDIAL-SIN syntactic annotation: general aims, parsing procedures, the annotation system. Ultimately, the text casts light on the potential of the CORDIAL-SIN corpus as a tool for (dialect) syntactic inquiry.